Toward a framework of determinants of financial management and financial problems among university students - Falahati, Leila; Paim, Laily (Academic Journals, 2011)
This study examines the effect of financial socialization, financial knowledge, financial attitude, and socialization agents on predicting financial management among college students. The sample comprised 2,430 students in six public and five private universities across Malaysia, which were randomly selected for the study. A self-administered questionnaire was used as the data collection method. The results indicate that in order of rank, spendthrift attitude, financial socialization, secondary socialization agents, and financial knowledge predict financial management. In addition, the results indicate that, in order, spendthrift attitude, secondary socialization agents, conservative attitude and financial management predict financial problems among college students.